Formation of free acetaldehydes derived from lipid peroxidation in U937 monocyte-like cells - Pospíšil, Pavel; Prasad, Ankush; Belková, Julie; Manoharan, Renuka Ramalingam; Sedlářová, Michaela (Biochimica et biophysica acta. G, General subjects, 2024)
Acetaldehyde can be found in human cells as a byproduct of various metabolic pathways, including oxidative processes such as lipid peroxidation. This secondary product of lipid peroxidation plays a role in various pathological processes, leading to various types of civilization diseases. In this study, the formation of free acetaldehyde induced by oxygen-centred radicals was studied in monocyte-like cell line U937. Exposure of U937 cells to peroxyl/alkoxyl radicals induced by azocompound resulted in the formation of free acetaldehyde. Acetaldehyde is formed by the cleavage of fatty acids, which represents the breakdown of fatty acids into smaller fragments initiated by the cyclization of lipid peroxyl radical and β-scission of lipid alkoxyl radical. The cleavage of fatty acids alters the integrity of the plasma and nuclear membrane, leading to the loss of cell viability. Understanding the pathological processes of acetaldehyde formation is an active area of research with potential implications for preventing and treating various diseases associated with oxidative stress.
Keywords: U937 Cells; Acetaldehyde; U937 buňky; Monocytes; reaktivní formy kyslíku; peroxidace lipidů; monocyty; mastné kyseliny; Humans; Free Radicals; lidé; volné radikály; Lipid Peroxidation; acetaldehyd; Reactive Oxygen Species; Fatty Acids